Mechanism of an Organoboron-Catalyzed Domino Reaction: Kinetic and Computational Studies of Borinic Acid-Catalyzed Regioselective Chloroacylation of 2,3-Epoxy Alcohols - Garrett, Graham E; Tanveer, Kashif; Taylor, Mark S (Journal of organic chemistry, 2017)
A mechanistic study of the borinic acid-catalyzed chloroacylation of 2,3-epoxy alcohols is presented. In this unusual mode of catalysis, the borinic acid activates the substrate toward sequential reactions with a nucleophile (epoxide ring-opening by chloride) and an electrophile (O-acylation of the resulting alkoxide). Reaction progress kinetic analysis of data obtained through in situ FTIR spectroscopy is consistent with a mechanism involving turnover-limiting acylation of a chlorohydrin-derived borinic ester. This proposal is further supported by investigations of the effects of aroyl chloride substitution on reaction rate. The kinetics experiments also shed light on the effects of chloride concentration on reaction rate and indicate that the catalyst is subject to inhibition by the product of the chloroacylation reaction. Computational modeling is employed to gain insight into the effects of the organoboron catalyst on the regioselectivities of the epoxide ring-opening and acylation steps. The density functional theory calculations provide a plausible pathway for selective chlorinolysis at C-3 and benzoylation at O-1, as is observed experimentally.